Peran Ruang Terbuka Hijau dalam Pembangunan Kota - nurul fitria marina (Retii, 2019)
Urban development is not only the construction of roads and buildings, but also the application of sustainable cities as a problem solutions, one of the problems is flood. The solution to reduce the flood, in addition by increasing the volume of the channel, is also by the use of rainwater and water conservation. Water conservation can be obtained by utilizing the role of green open space as water absorption as well as a shade, bad air filtering, and aesthetics. The existence of green open space in Indonesia needs to consider its procurement and its effectiveness against pollution from motorized vehicles, in view of the number of motorized vehicles and the driving needs to thesociety. The increasing need for roads and transportation accompanied by urban development has made the existence of green open space (GOS) increasingly declined. So that the pollution generated from motorized vehicles cannot be cleaned optimally by the environment. However in the recent years, several countries have promoted the provision of GOS as clean air filters. One of them is South Korea where the provided GOS is also able to reduce the congestion and improve the city's economy. While in Indonesia, Surabaya cityis known to have promoted the GOS program in the form of active parks, but is still not optimally utilized by the residents of Surabaya City. Whereas the residents in Seoul can utilize city parks as a means to relax themselves (due to the function of plants that are able to give a relaxation), socialize and be cultured (as a function of public space). Keywords: green open space, sustainable city, Surabaya, Seoul